Integrating eye health training into the primary child healthcare programme in Tanzania: a pre-training and post-training study. Issue 1 (9th July 2020) - Malik, Aeesha N J; Mafwiri, Mlika; Gilbert, Clare; Kim, Min J; Schellenberg, Joanna
Abstract : Objectives: To evaluate a primary child eye care training module for use in the WHO/UNICEF Integrated Management of Newborn and Childhood Illness (IMNCI) programme by primary healthcare workers. Design: Pre-training and post-training study. Setting: Primary healthcare facilities in a semirural district, central Tanzania. Participants: 54 primary healthcare workers selected by the Ministry of Health were trained during routine IMNCI training. All these healthcare workers were assessed pre-intervention and post-intervention. A subgroup of 40 were also assessed 6 months after the completion of training. Intervention: Training in an IMNCI eye module, developed for child primary healthcare workers with the Tanzania Ministry of Health and eye care experts. Main outcome measures: Knowledge, skills and attitudes were assessed using multiple choice questions, case studies and a self-assessment of skills using a Likert scale before and immediately after training, and 6 months later. A total score was derived. At 6 months, attitudes were assessed in semistructured interviews. Results: 69% PHWs trained were nurses. The baseline (before training) score was 29.9 (95% CI 27.5 to 32.4) and increased by 11.2 points (95% CI 8.3 to 14) immediately after training, and by 12.4 points (95% CI 9.2 to 15.6) at 6 months post the training. Therefore, the post-training scores increased and there was no evident difference in scores from immediately after training to 6 months later. Self-assessed confidence in skills decreased from 9/18 (95% CI 9 to 10) to 6/18 (95% CI 6 to 7). At 6 months, the module was reported as easy to understand and use, with challenges including difficulties in examining children's eyes and poor referral systems. Conclusions: The module increased knowledge of child eye health in primary healthcare workers, which was maintained, and was acceptable. The module has since been included into the national IMNCI health policy in Tanzania.